2015
DOI: 10.1080/21624054.2015.1129486
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuit rewiring: insights from DD synapse remodeling

Abstract: Nervous systems exhibit many forms of neuronal plasticity during growth, learning and memory consolidation, as well as in response to injury. Such plasticity can occur across entire nervous systems as with the case of insect metamorphosis, in individual classes of neurons, or even at the level of a single neuron. A striking example of neuronal plasticity in C. elegans is the synaptic rewiring of the GABAergic Dorsal D-type motor neurons during larval development, termed DD remodeling. DD remodeling entails mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
(63 reference statements)
2
17
0
Order By: Relevance
“…An ongoing effort to produce a gene expression fingerprint of each type of C. elegans neuron (Hammarlund et al, 2018; Taylor, 2019) may be useful for identifying genetic programs that uniquely correlate with spine morphogenesis since only a small number (White et al, 1976) of neurons have been reported to have spine-like structures. Finally, a developmentally regulated remodeling program (Kurup and Jin, 2016; Petersen et al, 2011; White et al, 1978) transforms presynaptic boutons into postsynaptic spines in larval DD neurons and thus could be especially useful for live imaging studies of synaptic plasticity and spine morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…An ongoing effort to produce a gene expression fingerprint of each type of C. elegans neuron (Hammarlund et al, 2018; Taylor, 2019) may be useful for identifying genetic programs that uniquely correlate with spine morphogenesis since only a small number (White et al, 1976) of neurons have been reported to have spine-like structures. Finally, a developmentally regulated remodeling program (Kurup and Jin, 2016; Petersen et al, 2011; White et al, 1978) transforms presynaptic boutons into postsynaptic spines in larval DD neurons and thus could be especially useful for live imaging studies of synaptic plasticity and spine morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of IF Genes That Regulate Synapse Rewiring. At the end of larval stage 1 (L1), the dorsal D (DD)-type motor neurons rewire their presynaptic connections from the ventral nerve cord (VNC) to the dorsal nerve cord (DNC), concurrent with the birth of ventral D (VD)-type motor neurons, which then form synapses along the VNC (19). We visualized DD-neuron presynaptic terminals using a GFP-tagged synaptobrevin (SNB-1::GFP) reporter (juIs137: P flp-13 SNB-1::GFP).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, DD rewiring is integral to maturation of the motor circuit. This dramatic synaptic rewiring offers a powerful model in which we can identify genes that are essential for the developmental plasticity of neurons (Kurup and Jin, 2016). …”
Section: Introductionmentioning
confidence: 99%